The clinical characteristics and implications of acute kidney injury during induction therapy for acute promyelocytic leukemia - Shen, Kai; Yang, Chenlu; Huang, Jie; Shuai, Xiao; Niu, Ting; Ma, Hongbing (Frontiers in Pharmacology, 2025)
BackgroundDual induction with all-trans retinoic acid (ATRA) and arsenic trioxide (ATO) has made acute promyelocytic leukemia (APL) a curable disease. However, differentiation syndrome (DS) can be a life-threatening complication of induction therapy. It is considered to result from a severe systemic inflammatory response mediated by increased expression of cytokines, chemokines, and adhesion molecules on differentiating blast cells. The kidney, as a vital organ rich in the capillary endothelium, could be targeted by differentiating blasts in DS. Acute kidney injury (AKI) is a rare but severe consequence of DS secondary to ATRA and ATO induction and can result in renal failure and early mortality. Nevertheless, its clinical characteristics and impact on APL prognosis have yet to be elucidated.ObjectivesThe aim of this study was to describe the clinical characteristics of DS-related AKI in patients with APL and its impact on patient prognosis.MethodsThis was a retrospective study from a single center in a real-world setting. APL patients who developed AKI during ATRA- and ATO-based induction were included. The patients’ clinical/laboratory data and outcome information were retrieved from the electronic medical records.ResultsFrom January 2011 to March 2024, a total of 26 out of 572 (4.5%) APL patients were identified as having AKI during dual induction. Among them, eight patients received continuous renal replacement therapy, and 3/8 patients experienced early death (ED), which was defined as death within 3 months of diagnosis. Among the five non-ED patients, three did not recover from renal function and were still dialysis-dependent during the follow-up. The estimated 2-year overall survival rate for all patients was 42%, and the ED rate was 30.8%. Survival analysis revealed that a greater tumor burden, a rapidly increasing WBC count, worse coagulation parameters, and persistent renal dysfunction were associated with a more adverse prognosis.ConclusionAKI is a rare but severe complication of DS in the ATRA + ATO dual-induction era of APL. It is associated with a high ED rate and dismal long-term survival. Some patients develop irreversible renal dysfunction and become dialysis-dependent after leukemia remission. Thus, the management of AKI in APL patients is still a clinical challenge, and a deeper understanding of its pathogenesis, along with multidisciplinary efforts, is needed.